Macronutrient Digestibilities and Enzyme Activities in Rumen Fluid Supplemented by Protein-Energy Synchronized Index-Based Rations - Afduha Nurus Syamsi; Harwanto Harwanto; Hermawan Setyo Widodo; Yusuf Subagyo (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The protein-energy synchronized (PES) index-based rations can optimize microbial protein synthesis (MPS) and affect enzyme activity and macronutrient digestibility of ration in rumen fluid. This study aimed to examine the in vitro effect of a ration based on PES index on macronutrient digestibility and enzyme activity in rumen fluid. The research was conducted experimentally, consisting of 4 treatment rations with different PES indexes (R1: 0.55; R2: 0.6; R3: 0.65; R4: 0.7). Each treatment was repeated 5 times, so there were 24 experimental units. The material used was the rumen fluid of the Jawa Randu Goat, which was taken at the Sokaraja Slaughterhouse shortly after the goat was slaughtered. Each ration consisted of napier grass, river tamarind, coconut meal, soybean dregs, rice bran, cassava waste, and mineral mix. The results showed that the PES index significantly affected (P<0,01) the digestibility of protein (A), fiber (B), and fat (C), as well as the activity of protease (D) and cellulase (E) enzymes. Theorthogonal polynomial test showed that the PES index has a quadratic effect on all test parameters with the following equation: A (Y= -1229.5X2 + 1540.6X -457.57; R2= 0.75), B (Y = -800.95X2+ 955.86X -264.51; R² = 0.75), C (Y = 868.92X2-1038.2X + 325.1; R2= 0.81), D (Y = -41.4X2+ 51.697X -14.982; R² = 0.77), and E (Y = -4.8538X2+ 5.927X -1.6241; R² = 0.84). The protein-energy synchronized index-based rations increased the in vitro of macronutrient digestibility (protein, fiber, and fat) and enzyme activity on rumen fluid at a medium index level (0.6-0.63).